Analysis of changes in purchase intention of electric vehicles due to the spread of ICT-based sharing and reservations for in-town recharging facilities - Kyoko Manaka; Hinata Kikuchi; Akihiro Nakamura (International Telecommunications Society (ITS), 2024)
Efforts to promote the widespread adoption of electric vehicles (EVs), which contribute to the realization of a carbon-neutral society, are being discussed. According to the Japan Automobile Dealers Association, the share of EVs in new passenger car sales was approximately 1.16% in the period ending December 2024, with a total share of about 1.85%. Past surveys related to Battery Electric Vehicles (BEVs)indicate that factors such as driving range and vehicle specifications, as well as the availability of charging facilities, are key to their widespread adoption (Pysalska et al., 2022; Phillipsen et al., 2020; Khan et al., 2017; Kudoh and Motose, 2010). There are different types of EV charging facilities, such as regular recharging facilities which take several hours to charge for a 100 km drive and fast charging facilities which take about 30 minutes to charge for a 100 km drive. The installation cost of the former is relatively low, and it can be installed in individual homes using subsidies. In contrast, the installation cost of the latter ranges from 10 to 20 million yen, making it impractical for individual homes and used by the public in a manner similar to current gasoline stations. Additionally, there are Super-fast charging facilities called Superchargers, dedicated to Tesla vehicles, which allow significantly faster charging than fast charging facilities. Currently, fast charging facilities are mainly installed in locations such as automobile dealerships, convenience stores, roadside stations, and expressways (SA/PA), with 40% of installations at automobile dealerships, while only 10% are at convenience stores and roadside stations/highways (Source: March 2023, e-mobility power charging spot list). On the other hand, regular recharging facilities are installed mainly in destinations with long stay times such as hotels and shopping malls, in addition to individual home installations. The necessity for adequate recharging facilities is evident as BEV usage can only become widespread if users have convenient access to recharging options. In Japan, over 29,000 recharging facilities exist, with approximately 70% being regular recharging facilities and 30% being fast recharging facilities. It is relatively easy to install in detached houses but challenging in apartment buildings. According to the "Housing and Land Statistics Survey" by the Statistics Bureau of Japan in 2018, 53.6% of households live in detached houses, and 43.5% live in apartment buildings, with the percentage of apartment dwellers reaching 71% in Tokyo. This higher ratio in urban areas presents a challenge to the widespread installation of charging facilities. While installing regular recharging facilities in individual homes is relatively easy, in apartment-type residences, it is necessary to obtain approval from the residents' association, which is organized by the inhabitants, to install charging facilities in communal parking areas. these households face significant constraints in installing personal recharging stations in their parking spaces. This is one reason why apartment dwellers hesitate to purchase BEVs. Charging facilities remain idle when not in use and are suitable for shared use. In fact, public fast recharging facilities are used as shared infrastructure. While regular recharging facilities are generally installed in individual homes and are not typically considered for shared use, the advancement of ICT and the widespread ownership of smartphones suggest that shared use of regular recharging facilities in individual homes would be quite feasible. Previous studies highlight the critical role of ICT in optimizing various services and systems, including transportation. For instance, Benevolo et al. (2016) and Jittrapirom et al. (2017) emphasize how ICT can enhance smart mobility and user-centered mobility services. Breidbach and Brodie (2017) discuss the sharing economy's reliance on ICT for facilitating value co-creation and engagement. Billhardt et al. (2019) demonstrate how ICT improves the matching efficiency of cab dispatch services. These studies would indicate that ICT may contribute the matching efficiency of recharging facilities online. In Japan, currently, it is possible to search for recharging facilities online, but there are not many facilities that can be reserved via apps. If recharging facilities become more widely available, and if it becomes possible to check their real-time availability and make reservations using a smartphone app, this is likely to increase the willingness to purchase EVs. Especially in Japanese urban areas with a high ratio of apartment dwellers, the efficient use of infrastructure, including regular recharging facilities, is essential for high EV adoption rates. Based on this awareness, this study aims to explore the impact of enhanced availability of charging facilities, such as through sharing and online reservations, on the intention to purchase BEVs in urban areas of Japan with high apartment dwelling ratios.
Keywords: 330